Aquaponia como fonte de produção e renda na comunidade bom fim, Angicos/RN - Oliveira, Ítala Marine Silva de (Universidade Federal Rural do Semi-Árido, 2019)
Poor water availability in the northeastern semi-arid region makes life difficult for small farmers, and it is often not possible to acquire income through production, becoming even more harder, to acess food that guarantee food secutiry. This study aimed to verify the technical feasibility of implementing an aquaponic project, as well as the possibility of income generation through it. The project is intended for a community in the northeastern semi-arid region, where a group of farmers of 12 families, living on subsistence agriculture, live. An aquaponic system was proposed using the media bed cultivation technique, cultivating Nile tilapia, lettuce, tomato, basil, parsley and coriander is proposed. Where it was possible, through the protein demand of the community under study, to desing the project, estimating the size of the essential components of an Aquaponics system. By through simulations, the project's implementation capacity has been proven and income generation for the community, making use of a watersaving system and providing the right to food, strongly contributing to the sustainable development goals (SDG).
Monografia
Keywords: Produção de peixes e vegetais; Semiárido; Segurança alimentar; Técnica sustentável; Fish and vegetable production.; Semiarid; Food security; Sustainable technique; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA